Assessing the utility of Xpert® MTB/RIF as a screening tool for patients admitted to medical wards in South Africa - Heidebrecht, Christine L.; Podewils, Laura J.; Pym, Alexander S.; Cohen, Ted; Mthiyane, Thuli; Wilson, Douglas (Scientific reports, 2016)
Many hospital inpatients in South Africa have undiagnosed active and drug-resistant tuberculosis (TB). Early detection of TB is essential to inform immediate infection control actions to minimize transmission risk. We assessed the utility of Xpert ® MTB/RIF (GeneXpert) as a screening tool for medical admissions at a large public hospital in South Africa. Consecutive adult patients admitted to medical wards between March-June 2013 were enrolled; sputum specimens were collected and tested by GeneXpert, smear microscopy and culture. Chest X-rays (CXRs) were conducted as standard care for all patients admitted. We evaluated the proportion of patients identified with TB disease through each diagnostic method. Among enrolled patients whose medical charts were available for review post-discharge, 61 (27%) were diagnosed with TB; 34 (56% of diagnosed TB cases) were GeneXpert positive. When patients in whom TB was identified by other means were excluded, GeneXpert yielded only four additional TB cases. However, GeneXpert identified rifampicin-resistant TB in one patient, who was initially diagnosed based on CXR. The utility of GeneXpert for TB screening was limited in an institution where CXR is conducted routinely and which serves a population in which TB and TB/HIV co-infection are highly prevalent, but it allowed for rapid detection of rifampicin resistance.